The Regulation of the CNS Innate Immune Response Is Vital for the Restoration of Tissue Homeostasis (Repair) after Acute Brain Injury: A Brief Review - M. R. Griffiths; P. Gasque; J. W. Neal (International Journal of Inflammation)
Neurons and glia respond to acute injury by participating in the CNS innate immune response. This involves the recognition and clearance of “not self ” pathogens and “altered self ” apoptotic cells. Phagocytic receptors (CD14, CD36, TLR–4) clear “not self” pathogens; neurons and glia express “death signals” to initiate apoptosis in T cells.The complement opsonins C1q, C3, and iC3b facilitate the clearance of apoptotic cells by interacting with CR3 and CR4 receptors. Apoptotic cells are also cleared by the scavenger receptors CD14, Prs-R, TREM expressed by glia. Serpins also expressed by glia counter the neurotoxic effects of thrombin and other systemic proteins that gain entry to the CNS following injury. Complement pathway and T cell activation are both regulated by complement regulatory proteins expressed by glia and neurons. CD200 and CD47 are NIRegs expressed by neurons as “don't eat me” signals and they inhibit microglial activity preventing host cell attack. Neural stem cells regulate T cell activation, increase the Treg population, and suppress proinflammatory cytokine expression. Stem cells also interact with the chemoattractants C3a, C5a, SDF-1, and thrombin to promote stem cell migration into damaged tissue to support tissue homeostasis.